Depressive symptomatology after spinal cord injury: A multi-center investigation of multiple racial-ethnic groups. (2nd January 2017) - Cao, Yue; Li, Chao; Gregory, Anne; Charlifue, Susan; Krause, James S.
Abstract : Objective : To identify (1) racial-ethnic differences in depressive symptomatology after spinal cord injury (SCI) and (2) the relationship of multiple additional factors to depressive symptoms, including health behaviors, employment, fatigue, and pain interference. Design : Cross-sectional Setting : Data were collected at 3 specialty hospitals in different regions of the USA (Southeastern, Mountain, Western). Participants : Participants (N = 1, 063) were identified from outpatient records of the 3 hospitals with oversampling of racial-ethnic minority groups. Interventions : N/A Main Outcome Measure(s) : The outcome, depressive symptomatology, was measured by the Older Adult Health and Mood Questionnaire (OAHMQ). Participant demographic and injury characteristics were measured as statistical controls, as well as other variables including health behavior factors, depression/stress relief medication usage, fatigue, and pain interference. The multivariate analyses were developed using OLS regression models and logistic regression models. Results : Employment was protective for depressive symptomatology, whereas fatigue, pain interference, and binge drinking were risk factors for higher OAHMQ scores. Although there were no bivariate racial-ethnic differences in depressive symptoms, fatigue and pain interference had suppression effects on the relationship between race-ethnicity and depressive symptomatology. After controlling for fatigue and pain interference, Hispanic participants had significantly lower OAHMQ scores and lower odds of probable major depression (PMD) than non-Hispanic Whites and Blacks. Conclusions : Fatigue and pain interference are associated with both race-ethnicity and depressive symptomatology. Assuming the same level of fatigue and pain interference, Hispanics will have a lower risk of depressive symptoms than non-Hispanic Whites and Blacks.